Smart home application for home based gardening - Mohamed Nijamudeen Peer Mohamed (Nanyang Technological University, 2021)
There is an increasing need for humanity to become more involved in caring for the environment and nature. This responsibility trickles down from governments and organizations all the way to individuals. Out of the many possible ways that individuals can do their part for nature would be to grow their own plants under their own roof. This however is hindered by the lack of knowledge or time to tend for these plants. Given the prevalence of technology around us as well as uninterrupted access to a smart device, it should be possible to isolate and deal with the individual aspects of caring and nurturing for plants through the help of these smart devices. Easily accessible sensors can be paired together with a microcontroller than can gather the various reading, which will be sent to a server which will determine if the plant has sufficient resources and will then instruct the microcontroller to supplement any limited resource. The overarching process can be viewed through the website, which will present a summary of their plants while giving them control over the resources the plant is supplemented with. The hardware system consists of a moisture sensor, temperature sensor, light sensor which collects the relevant readings, which then will be used to determine which of the two relays, pump and grow light, should be switched on.